Hubungan Variasi Menu, Persepsi Besar Porsi dengan Asupan Energi Terhadap Status Gizi Narapidana: Relationship Between Menu Variety, Perception of Portion Size and Energi Intake on the Nutritional Status of Prisoners - Ni Putu Sintha Dewi Aqnie; Rijanti Abdurrachim (UNIVERSITAS NGUDI WALUYO, 2024)
Correctional institutions often have over capacity, South Kalimantan has over capacity reaching 255%. Pelaihari Class IIB State Detention Center is in 2nd place with excess capacity, namely 263.2%. The Pelaihari Detention Center does not yet have a Nutritionist whose job is to oversee the administration of food so that it affects intake and has an impact on the nutritional status of inmates. The aim of the study was to determine the relationship between menu variations, perceptions of portion size and energy intake on the nutritional status of prisoners. The aim of the study was to determine the relationship between menu variations, perceptions of portion size and energy intake on the nutritional status of prisoners. This research is an analytic observational with a cross sectional approach tested statistically using Spearman's rank. The sample is convicts in January - June 2022 with a total of 46 respondents. This research was conducted in April 2023 and located in the Class IIB Pelaihari Detention Center. The research variables are menu variations, perceptions of portion size, and energy intake of prisoners by interviewing questionnaires. The results of the study were that respondents rated menu variations as not varied, namely 45.7%, perceptions of portion sizes were not appropriate 31%, and good energy intake 82.6%. BMI calculation results normal nutritional status 78.3%. There is no relationship between menu variety and energy intake (p=0.060), there is no relationship between perceived portion size and energy intake (p=0.568) and there is a relationship between energy intake and nutritional status (p=0.018). Inmates at the Pelaihari Detention Center are expected to eat the food served at the detention center so that daily intake can be fulfilled optimally and nutritional status remains normal. ABSTRAK Lembaga pemasyarakatan sering terjadi over kapasitas, Kalimantan Selatan over kapasitas mencapai 255%. Rumah Tahanan Negara Kelas IIB Pelaihari menduduki urutan ke-2 kelebihan kapasitas yaitu 263,2%. Rutan Pelaihari belum memiliki Ahli Gizi yang bertugas mengawasi penyelenggaraan makanan sehingga mempengaruhi asupan dan berdampak pada status gizi narapidana. Tujuan penelitian mengetahui hubungan variasi menu, persepsi besar porsi dengan asupan energi terhadap status gizi narapidana. Penelitian ini merupakan observasional analitik dengan pendekatan Cross Sectional diuji statistik menggunakan rank Spearman. Sampel adalah narapidana pada bulan Januari – Juni 2022 sebanyak 46 responden. Penelitian ini dilaksanakan pada bulan April 2023 dan lokasi di Rutan Kelas IIB Pelaihari. Variabel penelitian yaitu variasi menu, persepsi besar porsi, dan asupan energi narapidana dengan wawancara kuesioner. Responden menilai variasi menu tidak bervariasi yaitu 45,7%, persepsi besar porsi kurang sesuai 31%, dan asupan energi baik 82,6%. Hasil perhitungan IMT status gizi normal 78,3%. Hubungan variasi menu dengan asupan energi menunjukkan tidak ada hubungan yang signifikan (p=0,060), persepsi besar porsi dengan asupan energi menunjukkan tidak ada hubungan yang signifikan (p=0,568) dan asupan energi dengan status gizi menunjukkan hubungan yang signifikan (p=0,018). Narapidana di Rutan Pelaihari diharapkan menghabiskan makanan yang disajikan dirutan agar asupan harian dapat terpenuhi secara optimal dan status gizi tetap normal.